Effects of oxidation and nitridation temperatures on electrical properties of sputtered Zr thin film based on Si in N2O ambient - Wong, Y.H.; Cheong, K.Y. (Springer Verlag (Germany), 2012)
The effects of oxidation and nitridation temperatures (500–1100°C) on metal-oxide-semiconductor characteristics of sputtered Zr thin film on Si in N2O ambient have been systematically investigated. The sample being oxidized and nitrided at 700°C has demonstrated the highest effective dielectric constant of 21.82 and electrical breakdown field of 13.6 MV cm−1 at a current density of 10−6 A cm−2. This is attributed to the lowest effective oxide charge, interface-trap density, and total interface-trap density of the oxide and the highest barrier height of conduction band offset between the oxide and semiconductor when compared with others.